SEXUALITY, DIVERSITY AND LAW: THE LEGAL PROTECTION OF SEXUAL EXPRESSIONS - Silva Galdino, Valéria; Costa Cazelatto, Caio Eduardo (Revista Brasileira de Direito Animal, 2020)
The social and juridical contours attributed to the values and expressions of human sexuality are the constant target scientific discussions, especially when this attention is focused on sexual diversity. As a result of this, the present research had bibliographical and narrative reviews in order to investigate the legal protection of sexuality, above all, that related to the experience of sexual minorities. For that, the historical, conceptual and classificatory aspects about the theme were explored as well as sexuality, discussed as a fundamental right and personality, since its exercise is immanent to the human condition.